TIME-RESOLVED PHOTOLUMINESCENCE FOR QUANTUM WELL SEMICONDUCTOR HETEROSTRUCTURES - Ryan, J (1985)
Time-resolved photoluminescence spectroscopy with picosecond time resolution is currently being used to study the dynamics of photoexcited hot carriers confined in quantum well (QW) heterostructures. The energy relaxation of hot carriers in modulation-doped GaAs QW has been measured and the electron-LO phonon scattering rate is found to be substantially smaller than in the bulk. The experimental evidence is reviewed, and theoretical models incorporating screening of the e-LO phonon interaction and hot phonon effects are discussed. When a magnetic field is applied normal to the heterojunction the carrier motion is fully quantized. Recent time-resolved experiments which have measured the effect of magnetic fields on the energy relaxation rate are described. In undoped QW structures excitonic recombination dominates the emission spectrum; time-resolved photoluminescence experiments show that the exciton energy relaxation rate is significantly slower than that predicted by deformation potenial scattering. © 1985.